2021
DOI: 10.2147/opth.s299098
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Ocular Hypertension/Glaucoma After Descemet Stripping Automated Endothelial Keratoplasty

Abstract: To evaluate the incidence, demographics, associated risk factors, management and clinical outcomes of ocular hypertension/glaucoma after Descemet stripping automated endothelial keratoplasty (DSAEK). Methods: A cohort review of 81 DSAEK cases was performed at Queen Victoria Hospital, United Kingdom. Patients with pre-existing glaucoma, transient increased IOP within the first 48 hours post-graft, additional post-transplant surgery, or failed to complete one year follow-up were excluded from the study. Ocular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The incidence of post-DSAEK ocular hypertension was reported as 51.9%, including steroid-induced IOP elevation [ 23 ]. The authors also found that pseudophakia ( p = 0.024) and preoperative IOP > 16 ( p = 0.003) were risk factors of post-DSAEK ocular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of post-DSAEK ocular hypertension was reported as 51.9%, including steroid-induced IOP elevation [ 23 ]. The authors also found that pseudophakia ( p = 0.024) and preoperative IOP > 16 ( p = 0.003) were risk factors of post-DSAEK ocular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Elalfy et al . [ 11 ] showed that all eyes with steroid-induced IOP elevation were on the highest potency of steroid drop, dexamethasone 0.1%, and the earliest onset of IOP elevation was seen within a week. Steroid-induced IOP elevation could normally be controlled by tapering steroids, changing steroids, or starting antiglaucoma medication.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of elevated IOP requiring treatment in eyes having undergone fullthickness or lamellar corneal transplantation ranges from 6% to 54%. [1][2][3][4][5][6][7][8][9][10][11][12] Keratoplasty can exacerbate preexisting glaucoma or contribute to new-onset glaucoma. Mechanisms include long-term use of topical steroids, prolonged inflammation, tight sutures with distortion of the angle, as well as direct trauma to the trabecular meshwork (TM) and/or formation of peripheral anterior synechiae.…”
mentioning
confidence: 99%
“…Glaucoma and raised intraocular pressure (IOP) are known complications in eyes that have undergone previous corneal transplantation. The incidence of elevated IOP requiring treatment in eyes having undergone full-thickness or lamellar corneal transplantation ranges from 6% to 54% 1–12 . Keratoplasty can exacerbate preexisting glaucoma or contribute to new-onset glaucoma.…”
mentioning
confidence: 99%